Successful Elimination of Gallbladder Ascariasis by Conservative Therapy, Followed by Cholecystectomy due to Developing Cholecystitis - Ahmad Alhamid; Ziad Aljarad; Ahmad Ghazal; Ahmad Mouakeh; Ahmad Sankari Tarabishi; Majed Joudeh; Mohammad Mohammad; Aos Alhamid; Jawhar Aljarad; Maen Mousa (Case Reports in Gastrointestinal Medicine)
Background. Ascaris lumbricoides is the most common parasitic infection in human. The worm is usually located in the small intestine, but may invade into the pancreatic or biliary tree, but rarely into gallbladder because of the anatomic features of the cystic duct. Case Presentation. We report a case of gallbladder ascariasis that was diagnosed incidentally in a 70-year-old man, with negative ova and parasite test and no eosinophilia. We also compared echography and computerizied tomograph as diagnostic tools for gallbladder ascariasis. The patient was managed conservatively, but he underwent cholecyctectomy later because of developing cholecystitis. Conclusion. Depending on this case, we suggest cholecyctectomy as an initial management of gallbladder ascariasis.